2015
DOI: 10.1590/1981-863720150003000022893
|View full text |Cite
|
Sign up to set email alerts
|

Artificial teeth: evaluation of wear resistance, microhardness and composition

Abstract: ObjectiveTo evaluate the Knoop hardness, composition, and wear resistance of acrylic-resin artificial teeth exposed to mechanical toothbrushing. Methods Artificial under a 200-g load and at a frequency of 250 cycles per minute, using a soft-bristled toothbrush (IndicatorPlus 30, Oral-B) soaked in a 1:1 toothpaste/water slurry (Oral B Pró Saúde). Microhardness testing was performed using a 25-g load for 15 seconds in an HMV-2 hardness tester (Shimadzu). The composition of teeth from different brands was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…This increase of the free polymers affects the bond strength of these teeth with monomer of the heat-cured acrylic resin used for denture base [ 25 ]. A previous study showed that Trilux are composed essentially of carbon, oxygen, hydrogen (main elements), and silicon, but it has more silicon and carbon than other artificial teeth such as Biotone and Soluut [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase of the free polymers affects the bond strength of these teeth with monomer of the heat-cured acrylic resin used for denture base [ 25 ]. A previous study showed that Trilux are composed essentially of carbon, oxygen, hydrogen (main elements), and silicon, but it has more silicon and carbon than other artificial teeth such as Biotone and Soluut [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estudos prévios mostram que os métodos de higiene, como a escovação, podem interferir na integridade da superfície dos dentes artificiais de resina acrílica (FREITAS;PARANHOS, 2006;GRANDO et al, 2015;OLIVEIRA et al, 2013). A escovação pode provocar abrasão e um aumento da rugosidade superficial e esses fatores podem levar à perda de massa dos dentes artificiais, o que compromete a adaptação da prótese e a estética (PISANI et al, 2010;SORGINI, 2011).…”
Section: Discussionunclassified
“…A presença de irregularidades na superfície, que caracteriza o aumento da rugosidade superficial, foi encontrada neste estudo após a escovação, corroborando outros estudos (BRIGAGÃO; CAMARGO;NEISSER, 2005;FREITAS;PARANHOS, 2006;GRANDO et al, 2015;OLI-VEIRA et al, 2013;PISANI et al, 2010;SORGINI, 2011;), e mostrando, assim, que a integridade da resina acrílica pode ser danificada pela escovação, com aumento da rugosidade e perda de polimento.…”
Section: Discussionunclassified
“…Consani, Pucciarelli, Mesquita, Nogueira, and Barao (2014)[ 14 ] reported that different polymerization cycles have the same effect on the hardness of heat cure resin material. Grando, Pacheco, Botega, Hirakata, and Hilgert[ 15 ] reorted no significant difference in the wear resistance of different brands' (Trilux, Soluut PX) teeth. Akin, Kirmani, Tugut, and Coskum (2014)[ 16 ] worked upon the effects of different surface treatments in the ridge lap area of acrylic resin teeth on shear bond strength to heat polymerized poly (methyl methacrylate) (PMMA) denture base resin.…”
Section: Discussionmentioning
confidence: 99%